The Effect of Nutrition Education Through Media Booklet on Increasing Knowledge, Attitude and Behavior about Anemia on Adolescent Girls in Junior High School Negeri 1 Simpang Tiga Aceh Besar - Nabila Nabila; Arnisam Arnisam (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2022)
Anemia is a condition that often occurs in adolescent girls, which can be caused by various factors such as nutritional status, menstruation and socioeconomic status. Anemia can cause a person to experience a decrease in endurance and make the body susceptible to health problems. The prevalence of anemia in Aceh is 36.93% (Rikesdas, 2018). Based on this, providing education to young women can improve knowledge, attitudes and behavior so that they can handle cases of anemia in girls. This quantitative study uses a Quasi Experimental design. The subjects were taken as many as 34 Adolescent Girls, the sampling method was by the Proportional Simple Random Sampling Technique. The research location is in SMP Negeri 1 Simpang Tiga, the research was conducted in May 2022. Data collection includes primary and secondary data. Data analysis uses Dependent T-Test with 95% CI. Research data will be presented in tabular and textual form. The statistical test obtained a value of p = 0.001 on knowledge, p = 0.006 on attitude and p = 0.005 on behavior (p = <0.05) so that at CI: 95% Ho was rejected and Ha was accepted, it can be concluded that there is a significant effect of counseling with Booklet media on knowledge, attitudes and behavior. There is an effect of education with booklet media on knowledge, attitudes and behavior about anemia in SMP Negeri 1 Simpang Tiga.